2021
DOI: 10.3389/fcell.2021.634650
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Modulates the Crosstalk Between Macrophages and Bone Mesenchymal Stem Cells to Ameliorate Osteogenesis

Abstract: Bone healing is thought to be influenced by the cross-talk between bone forming and immune cells. In particular, macrophages play a crucial role in the regulation of osteogenesis. Curcumin, the major bioactive polyphenolic ingredient of turmeric, has been shown to regulate inflammatory response and osteogenic activities. However, whether curcumin could regulate macrophage polarization and subsequently influence osteogenesis remain to be elucidated. In this study, the potential immunomodulatory capability of cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 43 publications
(18 reference statements)
0
29
0
Order By: Relevance
“…To this end, the tailorable cues of biomaterials regarding surface topography, hydrophilicity, porosity, and materials dynamics and mechanics [ [35] , [36] , [37] ] can be considered for modulating the macrophage immune response. The main bioactive constituents of the traditional Chinese herbal medicines (e.g., Icariin [ 38 ], curcumin [ 39 ]) have also been applied to immunomodulation because of their anti-inflammatory properties and bone healing-enhancing effects. However, due to their complex chemical structure, the constituents are rarely used as a chemical synthesis component of biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the tailorable cues of biomaterials regarding surface topography, hydrophilicity, porosity, and materials dynamics and mechanics [ [35] , [36] , [37] ] can be considered for modulating the macrophage immune response. The main bioactive constituents of the traditional Chinese herbal medicines (e.g., Icariin [ 38 ], curcumin [ 39 ]) have also been applied to immunomodulation because of their anti-inflammatory properties and bone healing-enhancing effects. However, due to their complex chemical structure, the constituents are rarely used as a chemical synthesis component of biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Recent studies have illustrated that inducing anti-inflammatory macrophage (M2) polarization from M1 macrophage via biomaterials could suppress inflammatory immune cells and promote cartilage tissue regeneration by producing antiinflammatory factors, such as transforming growth factor-beta (TGF-𝛽) and interleukin-10 (IL-10). [9][10][11][12] For instance, Dai et al reported a double-network hydrogel based on squid cartilage type II gelatin and hyaluronic acid, which could control the M1/M2 phenotype switch and then stimulate the chondrogenesis of cartilage stem/progenitor cells through the M2 macrophage-mediated TGF-𝛽/Smad pathway. [13] Zhai et al demonstrated that a ceramic lithium calcium silicate scaffold promoted cartilage repair by upregulating the expression of IL-10 and suppressing the expression of inflammatory genes.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophage paracrine signalling is an important pathway that regulates BMSC osteogenic differentiation. The uptake of paracrine vesicles, exosomes, and other cytokines by BMSCs can upregulate the transcription levels of alkaline phosphatase (ALP), Runt-related transcription factor 2 (RUNX2), osteocalcin, and osteopontin and the protein expression levels of RUNX2 and osteocalcin, enhancing the activity of ALP ( Chen et al, 2021 ). Additionally, lipopolysaccharide-activated macrophages can promote the migration of BMSCs through paracrine IL-6 and inducible nitric oxide synthase ( Lei et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%